STUDYING THE FORMATION AND STABILIZATION OF CUR-AL+3 COMPLEXES BY USING CITRIC ACID AS CATALYST - Zina B. Muhammed; Tariq N. Musa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Cooking ware that is made of aluminum is used in different nations, particularly developing nations, and are a free source of aluminum. Due to its possible harmful effects on human health, aluminum is acknowledged as a public health problem. The goal of the current investigation is to evaluate curcumin’s (CUR) capacity to decrease aluminium’s toxicity by forming stable complexes. Rhizomes that are sold in the local marketplaces have an 8.5% crude pigment content of CUR. At various pH levels, CUR’s maximum absorbance was identified. Citric acid was used as a catalyst to create the CUR-Al+3 combination at various pH levels, which correspond to the rates at which Al+3 was eliminated from the solution. At pH 2.5, 3.0, 3.5, and 4.0, the highly complexation was seen. At such pH levels, the Al+3 elimination was 79.22, 78.28, 79.26, and 79.41%, respectively. The CUR-Al+3 complexes’ stability represent, respectively, 96.94, 96.29, 95.55, and 95.52% of the initial concentration at 25o, 50o, 75o, and 100o C for 60 min at pH value of 2.50. Using Fourier-transform infrared spectroscopy (FT-IR), it has been possible to identify CUR and its complex with Al+3. At varied pH levels, 1.5, 2.5, 3.5, 4.5, 5.5, and 6.5 at boiling point, the leached aluminium from 3 regions of the aluminium cooking ware (Syrian, Iranian and local) was specified. Comparatively to Syrian and local cooking wares, Iranian cooking ware generally leached more aluminum. In comparison to other pH values, the percentages of the elimination of the aluminum that is leached by utilizing the most leaching cookware (Iranian) have been 79.23 and 79.26% at pH values of 2.50 and 3.50, respectively.